Issues related to breastfeeding in the first six months of life in an urban tertiary care hospital - L., Manjula; Hegde, Jayashree (International Journal of Contemporary Pediatrics, 2017)
Background: Breastfeeding is being practiced since the existence of mammals on earth. Breastmilk can make the world healthier, smarter and more equal, it also saves lives of infants and reduces disease burden of both mother and infants. Common reasons for avoiding or stopping breastfeeding are medical, cultural, psychological, physical discomfort and inconvenience. This study was conducted to know the spectrum of problems related to breast feeding faced by mother-infant pairs in the first 6 months of life. Methods: A hospital based observational study was conducted in an urban tertiary care hospital from November 2010 to February 2012. Maternal and newborn data were obtained during postnatal period and they were later followed up in Pediatric Outpatient Department at regular intervals and information was also collected through telephonic conversation. Descriptive statistics were reported using mean, standard deviation or median, range for the continuous variable. Numbers and percentage were used for the categorical variable. Chi-square test or fisher’s exact test was done to test the association between the breast-feeding problems with demographical and clinical variables. p<0.05 was considered as significant. Results: Prelacteal feed was given to 17.7% babies, 30.9% mothers had breastfeeding problems. 41.3% babies were initiated on breastfeeding within one hour of birth. Parity (0.001) and mode of delivery (0.017) had significant association with breastfeeding problems. Conclusions: Breastfeeding issues like delayed initiation of breastfeeding, practice of prelacteal feeding, formula feeding, latching problems, perception of inadequate milk were noted. Parity and mode of delivery had an association with breastfeeding problems.